Regarding a solemn service in the Cathedral of Mexico, a Navarrese insurgent, and the lost score of a Catalan, based in The Colonial Havana. An excuse for an autoethnographic story and the biography of a musical document (Revista Argentina de Musicología, 2021)
To decode those elements (circumstances, background, events, invisible relationships, intellectual postures) that mediate the two-way interaction between the creative subject (life story) and artwork, musicology has expressed itself, among other genres, through the subject’s biography. Since the musical document, in its many variants, is evidence of the process of musical creation, I propose that, positioned from the management of cultural heritage, we write the object’s biography, deciphering, at the same time, contexts and reasons of the researcher and the investigated; paradox of the uniqueness of heritage work. As a result, the construction of this new knowledge supports a preservation that goes beyond data computation and factual description, revalidates that cultural good, and serves as a mediator for its refunctionalized insertion into the social practice of the music scene.
Keywords: musical document; musical heritage; cultural studies